1996
DOI: 10.1007/bf03164735
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow and vascular response to hypercapnia in hypertensive patients with leukoaraiosis

Abstract: Both arteriosclerosis and leukoaraiosis have a close relationship with hypertension, but the relationship between cerebral hemodynamics and leukoaraiosis in hypertensive patients has not been fully examined. To clarify this issue, we measured the regional cerebral blood flow (rCBF) and cerebrovascular response to hypercapnia in hypertensive patients with various degrees of leukoaraiosis. The subjects consisted of 7 normotensive normal controls and 17 hypertensive patients. The hypertensive patients were divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…[45][46][47] In demented patients, cortical CBF changes have been repeatedly reported in either a regional 38 or diffuse pattern. 37,42,48 The present negative findings might be related to the heterogeneity of our population, which included both demented and nondemented subjects. However, in contrast to the results obtained in white matter, we did not find a relationship between cortical blood flow and dementia in our patients.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…[45][46][47] In demented patients, cortical CBF changes have been repeatedly reported in either a regional 38 or diffuse pattern. 37,42,48 The present negative findings might be related to the heterogeneity of our population, which included both demented and nondemented subjects. However, in contrast to the results obtained in white matter, we did not find a relationship between cortical blood flow and dementia in our patients.…”
Section: Discussionmentioning
confidence: 76%
“…A larger decrease of CBF in white matter has been related to dementia in leukoaraiosis associated with other types of microangiopathy. 37,[42][43][44] Furthermore, Sabri et al 44 recently confirmed that cognitive impairment was related to CBF reduction in white matter but not to the extent of WMA in 57 patients with cerebral microangiopathy different from CADASIL. We recently reported, in vivo, that the severity of ultrastructural white matter changes was strongly related to the severity of clinical status in CADASIL.…”
Section: Discussionmentioning
confidence: 96%
“…Claus et al [34] also showed no relation between severity of WML and regional cerebral blood flow measured by single-photon emission tomography in 60 elderly subjects, most of whom had essential hypertension. Kuwabara et al [35] also reported a close relationship between cerebral hemodynamic reserve capacity, measured by positron emission tomography, and the severity of WML in hypertensive patients. Bakker et al [36] confirmed the association between decreased vasomotor reactivity and WML measured by means of a transcranial Doppler in 73 elderly individuals, 56% of whom were hypertensive.…”
Section: Cerebral Blood Flow and White Matter Lesionsmentioning
confidence: 89%
“…White matter lesions or leukoaraiosis are a hallmark of the radiological findings in VaD 15 and some authors have noted a lack of correlation between white matter disease and blood flow. Kubawara et al showed no differences in regional cerebral blood flow using positron emission tomography; 16 Sierra et al, using transcranial Doppler, found no difference in mean arterial velocity between patients with and without white matter disease. 17 An MR flow quantification study into dementia patients with and without white matter disease similarly found no significant correlation between flow and the degree of white matter disease.…”
Section: Resistancementioning
confidence: 97%